Flame-retardant thermoplastic resin and preparation method thereof

By using modified magnesium hydroxide as a flame retardant in thermoplastic resins, the problem of insufficient flame retardant performance of existing thermoplastic resins is solved, and the excellent flame retardant performance of thermoplastic resin composites is achieved, and its application range in high-demand fields is expanded.

CN119899442AInactive Publication Date: 2025-04-29HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311405567.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The flame retardant properties of existing thermoplastic resins are insufficient, which limits their applications in electronic and electrical equipment, automobiles, aerospace and other fields.

Method used

By synthesizing a modified magnesium hydroxide as a flame retardant and mixing it with thermoplastic resin, antioxidant and other components, a thermoplastic resin composite material with excellent flame retardant properties was prepared.

Benefits of technology

Modified magnesium hydroxide has better dispersion in thermoplastic resins, which significantly improves the flame retardant properties of thermoplastic resins, making them suitable for high-demand application fields.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses flame-retardant thermoplastic resin and a preparation method thereof. The flame-retardant thermoplastic resin is prepared from the following components in parts by weight: 96-116 parts of thermoplastic resin, 19-23 parts of a flame retardant and 0.1-0.5 part of an antioxidant, and the flame retardant is modified magnesium hydroxide. The invention also discloses a preparation method of the flame-retardant thermoplastic resin composite material. The 3, 4-dihydroxycinnamic acid is used for modifying magnesium hydroxide, and the polarity of magnesium hydroxide is weakened, so that the dispersity of magnesium hydroxide in the thermoplastic resin is improved, and the flame retardant effect of magnesium hydroxide is enhanced. The prepared thermoplastic resin composite material has very good flame retardant property, can be used in the field of automobile household appliance materials, and has very good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a flame retardant thermoplastic resin and a preparation method thereof. Background Art

[0002] Thermoplastic resin is a widely used polymer resin with advantages such as good fatigue resistance, good heat resistance and excellent dimensional stability. However, in some application fields, very high flame retardancy is required for thermoplastic resin. For example, in the fields of electronic and electrical equipment, automobiles, aerospace, etc., circuit breakers, connectors, battery modules and other materials have very high flame retardancy requirements, generally requiring to reach V0 level, and requiring to be able to inhibit or delay combustion while not being easy to burn itself, which limits the application of thermoplastic resin composite materials in these fields.

[0003] In view of these deficiencies, the present invention innovatively synthesizes a flame retardant thermoplastic resin composite material, which has excellent flame retardant properties and has very important practical significance for expanding the application field of thermoplastic resin composite materials. Summary of the invention

[0004] The invention innovatively synthesizes a flame retardant thermoplastic resin and a preparation method thereof, which has good flame retardant performance and solves the technical problem of limited flame retardant performance of thermoplastic resin in the prior art.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A flame retardant thermoplastic resin is composed of the following components in parts by weight:

[0007] Thermoplastic resin 96-116 parts

[0008] Flame retardant 19-23 parts

[0009] Antioxidant 0.1-0.5 parts

[0010] The flame retardant is modified magnesium hydroxide.

[0011] In a further embodiment, the thermoplastic resin is one of polyethylene (PE), polypropylene (PP), polystyrene (PS), polybutylene terephthalate (PBT), and polyamide 6 (PA6).

[0012] In a further embodiment, the modified magnesium hydroxide is prepared as follows:

[0013] (1) adding magnesium nitrate, sodium hydroxide and 3,4-dihydroxycinnamic acid into a solvent and reacting in a water bath to prepare a solution;

[0014] (2) Filtering, washing and drying the solution to obtain modified magnesium hydroxide.

[0015] In a further embodiment, the mass ratio of magnesium nitrate, sodium hydroxide and 3,4-dihydroxycinnamic acid is (30-40):(18-24):(1-3).

[0016] In a further embodiment, the solvent is acetone, ether or isopropanol

[0017] Preferably, the water bath reaction refers to reacting in a water bath at 50-70° C. for 10-12 hours.

[0018] The antioxidant is one or a mixture of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester (referred to as Irganox1010) produced by BASF of Germany, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine (referred to as Irganox1098) produced by Dow Chemical of the United States.

[0019] The second object of the present invention is to provide a method for preparing a flame retardant thermoplastic resin composite material, comprising the following steps:

[0020] (1) Weigh 96-116 parts of thermoplastic resin, 19-23 parts of flame retardant, and 0.1-0.5 parts of antioxidant, mix and stir evenly to obtain a mixture;

[0021] (2) Extruding the mixed material obtained in step (1) from an extruder and granulating it to obtain a thermoplastic resin composite material.

[0022] Since magnesium hydroxide has a high decomposition temperature, it can increase the heating temperature of polymer materials. In addition, the MgO generated after its combustion and dehydration is a refractory material and an alkaline oxide that can absorb acidic gases. Therefore, magnesium hydroxide is a new type of halogen-free flame retardant with strong heat absorption capacity and high flame retardant efficiency. However, due to the high polarity of magnesium hydroxide, adding it to thermoplastic resins will affect its dispersibility in thermoplastic resins, thereby affecting its flame retardant properties.

[0023] In this application, 3,4-dihydroxycinnamic acid is used to modify magnesium hydroxide, because magnesium hydroxide is Mg 2+ It is located in the center of the crystal nucleus, and the electronegativity of the hydroxide ion is different, so the direction of the electron cloud is biased towards the oxygen atom, making the hydrogen atom form a semi-exposed proton; the o-diphenol hydroxyl group contained in 3,4-dihydroxycinnamic acid can neutralize part of the hydrogen protons of magnesium hydroxide, thereby weakening the polarity of magnesium hydroxide, improving the dispersibility of magnesium hydroxide in thermoplastic resins, and thus enhancing the flame retardant effect of magnesium hydroxide.

[0024] Therefore, the modified magnesium hydroxide flame retardant prepared in the present application has better dispersibility than commercially available magnesium hydroxide, thereby making the thermoplastic resin have better flame retardancy, and can be used as a material in the field of automobiles and household appliances, and has a good application prospect. DETAILED DESCRIPTION

[0025] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0027] The raw materials used in the following examples are as follows:

[0028] PBT (model 1100-211M), Changchun Chemical Co., Ltd.;

[0029] PP (model Z30S), Sinopec Maoming Petrochemical Co., Ltd.;

[0030] PE (model 5070), Panjin Ethylene Co., Ltd.;

[0031] PA6 (Model IM), Kuibyshev Nitrogen (Shanghai) Engineering Plastics Co., Ltd.;

[0032] PS (model 350), Guo Qiao;

[0033] Magnesium hydroxide, Jinan Mingrun Chemical Co., Ltd.;

[0034] Magnesium nitrate, Shanxi Guangyuan Xinke Chemical Co., Ltd.;

[0035] Sodium hydroxide, Jinan Zhongcheng Chemical Co., Ltd.;

[0036] 3,4-Dihydroxycinnamic acid, Jinan Quanxing New Materials Co., Ltd.;

[0037] Acetone, ether or isopropanol, Jinan Xinchaorui Chemical Co., Ltd.;

[0038] Antioxidant S9228, Dow Chemical, USA;

[0039] Antioxidant (model Irganox1010, Irganox1098), BASF, Germany.

[0040] Preparation Example 1

[0041] (1) Weigh 300 g of magnesium nitrate, 180 g of sodium hydroxide, 10 g of 3,4-dihydroxycinnamic acid, and 700 g of solvent acetone, add them to a reaction vessel, and react in a 50° C. water bath for 10 h to prepare solution A;

[0042] (2) Filtering, washing and drying the solution A to obtain modified magnesium hydroxide, namely the flame retardant M1.

[0043] Example 1

[0044] (1) Weigh 96 parts of PP, 19 parts of flame retardant M1, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;

[0045] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material P1.

[0046] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 220r / min.

[0047] Comparative Example 1

[0048] (1) Weigh 96 parts of PP, 19 parts of commercially available magnesium hydroxide, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;

[0049] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D1.

[0050] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 220r / min.

[0051] The PP composite materials prepared in the above Example 1 and Comparative Example 1 were made into strips by injection molding and tested. The test data are as follows:

[0052] Test items Test Standards unit P1 D1 Flame retardant grade UL 94 V-0 V-2

[0053] It can be seen from the above table that the flame retardant property of the composite material prepared in Example 1 of the present application is better than that in Comparative Example 1.

[0054] Preparation Example 2

[0055] (1) Weigh 400 g of magnesium nitrate, 240 g of sodium hydroxide, 30 g of 3,4-dihydroxycinnamic acid, and 900 g of acetone solvent, add them to a reaction vessel, and react in a water bath at 70° C. for 12 h to prepare solution A;

[0056] (2) Filter, wash and dry solution A to obtain modified magnesium hydroxide, namely flame retardant M2.

[0057] Example 2

[0058] (1) Weigh 116 parts of PBT, 23 parts of flame retardant M2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant S9228, and 0.2 parts of antioxidant Irganox 1098, mix and stir evenly to obtain a mixture;

[0059] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material P2.

[0060] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 300r / min.

[0061] Comparative Example 2

[0062] (1) Weigh 116 parts of PBT, 23 parts of commercially available magnesium hydroxide, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant S9228, and 0.2 parts of antioxidant Irganox 1098, mix and stir to obtain a mixture;

[0063] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D2.

[0064] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 300r / min.

[0065] The PBT composite materials prepared in the above Example 2 and Comparative Example 2 were made into test strips by injection molding machine, and the test data are as follows:

[0066] Test items Test Standards unit P2 D2 Flame retardant grade UL 94 V-0 V-2

[0067] It can be seen from the above table that the flame retardant performance of Example 2 is better than that of Comparative Example 2.

[0068] Preparation Example 3

[0069] (1) Weigh 350 g of magnesium nitrate, 210 g of sodium hydroxide, 20 g of 3,4-dihydroxycinnamic acid, and 800 g of solvent ether, add them to a reaction vessel, and react in a water bath at 60° C. for 11 h to prepare solution A;

[0070] (2) Filter, wash and dry solution A to obtain modified magnesium hydroxide, namely flame retardant M3.

[0071] Example 3

[0072] (1) Weigh 106 parts of PE, 21 parts of flame retardant M3, 0.1 parts of antioxidant S9228, and 0.2 parts of antioxidant Irganox1010, mix and stir evenly to obtain a mixture;

[0073] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material P3.

[0074] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0075] Comparative Example 3

[0076] (1) Weigh 106 parts of PE, 21 parts of commercially available magnesium hydroxide, 0.1 parts of antioxidant S9228, and 0.2 parts of antioxidant Irganox 1010, mix and stir evenly to obtain a mixture;

[0077] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material D3.

[0078] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0079] The PE composite materials prepared in the above Example 3 and Comparative Example 3 were made into test strips by injection molding machine, and the test data are as follows:

[0080] Test items Test Standards unit P3 D3 Flame retardant grade UL 94 V-0 V-2

[0081] It can be seen from the above table that the flame retardant performance of Example 3 is better than that of Comparative Example 3.

[0082] Preparation Example 4

[0083] (1) Weigh 325 g of magnesium nitrate, 235 g of sodium hydroxide, 25 g of 3,4-dihydroxycinnamic acid, and 865 g of isopropanol as solvent, add them to a reaction vessel, and react in a water bath at 65° C. for 11 h to prepare solution A;

[0084] (2) Filter, wash and dry solution A to obtain modified magnesium hydroxide, namely flame retardant M4.

[0085] Example 4

[0086] (1) Weigh 97 parts of PA6, 19 parts of flame retardant M4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1098, mix and stir evenly to obtain a mixture;

[0087] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material P4.

[0088] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0089] Comparative Example 4

[0090] (1) Weigh 97 parts of PA6, 19 parts of commercially available magnesium hydroxide, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1098, mix and stir to obtain a mixture;

[0091] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material D4.

[0092] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0093] The PA6 composite materials prepared in the above Example 4 and Comparative Example 4 were made into strips by injection molding and tested. The test data are shown in the following table:

[0094] Test items Test Standards unit P4 D4 Flame retardant grade UL 94 V-0 V-2

[0095] It can be seen from the above table that the flame retardant performance of Example 4 is better than that of Comparative Example 4.

[0096] Preparation Example 5

[0097] (1) Weigh 385 g of magnesium nitrate, 215 g of sodium hydroxide, 28 g of 3,4-dihydroxycinnamic acid, and 865 g of acetone solvent, add them to a reaction vessel, and react in a water bath at 65° C. for 11 h to prepare solution A;

[0098] (2) Filter, wash and dry solution A to obtain modified magnesium hydroxide, namely flame retardant M5.

[0099] Example 5

[0100] (1) Weigh 105 parts of PS, 22 parts of flame retardant M5, 0.1 parts of antioxidant Irganox1010, and 0.1 parts of antioxidant S9228, mix and stir evenly to obtain a mixture;

[0101] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material P5.

[0102] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.

[0103] Comparative Example 5

[0104] (1) Weigh 105 parts of PS, 22 parts of commercially available flame retardant magnesium hydroxide, 0.1 parts of antioxidant Irganox1010, and 0.1 parts of antioxidant S9228, mix and stir to obtain a mixture;

[0105] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material D5.

[0106] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.

[0107] The PS composite materials prepared in the above Example 5 and Comparative Example 5 were made into strips by injection molding and tested. The test data are shown in the following table:

[0108] Test items Test Standards unit P5 D5 Flame retardant grade UL 94 V-0 V-2

[0109] It can be seen from the above table that the flame retardant performance of Example 5 is better than that of Comparative Example 5.

[0110] This shows that the thermoplastic resin composite material prepared by the method provided by the present invention has excellent flame retardant properties and can expand the application field of the thermoplastic resin composite material.

[0111] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0112] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A flame retardant thermoplastic resin composite material, characterized in that: It is composed of the following components by weight: Thermoplastic resin 96-116 parts Flame retardant 19-23 parts Antioxidant 0.1-0.5 parts The flame retardant is modified magnesium hydroxide.

2. The flame retardant thermoplastic resin composite material according to claim 1, characterized in that: The thermoplastic resin is polyethylene, polypropylene, polystyrene, polybutylene terephthalate or polyamide 6.

3. The flame retardant thermoplastic resin composite material according to claim 1, characterized in that: The modified magnesium hydroxide preparation steps are as follows: (1) adding magnesium nitrate, sodium hydroxide and 3,4-dihydroxycinnamic acid into a solvent and reacting in a water bath to prepare a solution; (2) Filtering, washing and drying the solution to obtain modified magnesium hydroxide.

4. The flame retardant thermoplastic resin composite material according to claim 3, characterized in that: The mass ratio of the magnesium nitrate, sodium hydroxide and 3,4-dihydroxycinnamic acid is (30-40):(18-24):(1-3).

5. The flame retardant thermoplastic resin composite material according to claim 2, characterized in that: The solvent is acetone, ether or isopropanol.

6. The flame retardant thermoplastic resin composite material according to claim 3, characterized in that: The water bath reaction refers to reacting in a water bath at 50-70° C. for 10-12 hours.

7. The flame retardant thermoplastic resin composite material according to claim 1, characterized in that: The antioxidant is at least one of bis(2,4-dicumylphenyl)pentaerythritol diphosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine.

8. A method for preparing a flame retardant thermoplastic resin composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Weigh 96-116 parts of thermoplastic resin, 19-23 parts of flame retardant, and 0.1-0.5 parts of antioxidant, mix and stir evenly to obtain a mixture; (2) Extruding the mixture obtained in step (1) from an extruder and granulating it to obtain a flame retardant thermoplastic resin composite material.

Citation Information

Patent Citations

  • Preparation of nano magnesium hydrate

    CN101376511A